Metodología juego-trabajo como estimulación del lenguaje para desarrollar aprendizajes significativos en los niños de 4-5 años de la Unidad Educativa “Francisco Huerta Rendón” del cantón Babahoyo - Maisincho Gorotiza, Allison Valeria (2022)
Currently, due to the pandemic that we are going through and that will possibly continue for many more years, the way of life of all human beings has changed drastically, changes in all aspects, however, in the area in which This case study will focus on the level of education that children and adolescents are receiving. Education has taken another direction, attendance at schools, colleges and universities has been left aside and replaced by attendance through a computer. Called virtual education, this modality brought with it as many benefits as disadvantages, in a certain sense it was personalized and both teachers and learners obtained a plus of comfort by attending to teach and receive classes from their homes, however, other aspects of education such as social interaction, touching science instruments, among other things, however, the most affected, as in any crisis, are children, because they are in a key stage of formation of their meaningful learning, where they depend on physical interaction , dynamics such as those developed in the play-work method to develop their motor skills and social development.